2016
DOI: 10.1021/acsami.5b12137
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoresponse of SnSe-Nanocrystals-Decorated WS2 Monolayer Phototransistor

Abstract: Single-layer WS2 has shown excellent photoresponse properties, but its promising applications in high-sensitivity photodetection suffer from the atomic-thickness-limited adsorption and band-gap-limited spectral selectivity. Here we have carried out investigations on WS2 monolayer based phototransistors with and without decoration of SnSe nanocrystals (NCs) for comparison. Compared to the solely WS2 monolayer, SnSe NCs decoration leads to not only huge enhancement of photoresponse in visible spectrum but also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 64 publications
3
65
2
Order By: Relevance
“…Due to such high responsivities, the phototransistors do not require any amplifiers. Figure 5 shows that the responsivity is proportional to the drain-source voltage, V ds , in the wide range of V ds [10,17]. This dependence is highly expected because the transit time is inversely proportional to V ds , and therefore, the photoconductive gain is proportional to V ds , i.e.…”
Section: Spectral Characteristics and Responsivitiesmentioning
confidence: 90%
See 2 more Smart Citations
“…Due to such high responsivities, the phototransistors do not require any amplifiers. Figure 5 shows that the responsivity is proportional to the drain-source voltage, V ds , in the wide range of V ds [10,17]. This dependence is highly expected because the transit time is inversely proportional to V ds , and therefore, the photoconductive gain is proportional to V ds , i.e.…”
Section: Spectral Characteristics and Responsivitiesmentioning
confidence: 90%
“…SnSe nanocrystals were combined with WS 2 monolayer in Ref. [17]. Copper indium sulfide QDs deposited on SnS 2 were studied in Ref.…”
Section: Hybrid Qd-2d Conductor Phototransistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single channel photodetector whose channel is a metal diselenide compound possessed a balanced performance exhibiting faster optical response than disulfide (commonly~100 Hz), but lower responsivity in the visible wavelength. Other exfoliated 2D TMDCs such as WS 2 [121,122], GaSe [123], GaS [124], ReS 2 [115,125], In 2 Se 3 [98,126,127], MoSe 2 [128], GaTe [129] have also been reported in high gain n-channel photodetectors. Mobility of these synthetic materials and the quality of the semiconductor/oxide interface are very important for photodetectors based on the CVD method, while the device fabrication process is almost the same as that on exfoliated films.…”
Section: Single Channel Photodetectorsmentioning
confidence: 99%
“…For TMDCs, single channel photodetectors, CVD synthesis with solid-phase metal oxide and sulfur precursors are widely used because of the easy synthesis approach, large single crystal domain, and high mobility. Photodetectors based on CVD MoS 2 [113,131], MoSe 2 [132,133], ReS 2 [63,114], ReSe 2 [134], SnS 2 [135,136], SnSe 2 [137], and WS 2 [110,122] have been studied recently. Jing et al reported a MoS 2 phototransistor array that can detect room light illumination [138].…”
Section: Single Channel Photodetectorsmentioning
confidence: 99%